Counseling Focus that Counselors Need to Understand in the Era of Society 5.0 - Syukur, Yarmis; Putra, Ade Herdian (International Journal of Applied Counseling and Social Sciences, 2024)
Along with the times, human problems are also increasingly complex. In the era of society 5.0, human problems, especially clients in counseling services, are also increasingly complex and unique. These problems need to be studied to determine the focus of counseling services by counselors. This study aims to explore the focus of counseling services in the era of Society 5.0. We use the Systematic Literature Review (SLR) method to explore the focus of counseling services in accordance with the current era. We examine various literature published since 1971 to the latest literature that discusses the focus of counseling services. We examine the literature to find out the development of focus in counseling services from time to time. The results of this study indicate that there are five counseling service focuses that need to be considered by counselors in the era of Society 5.0, namely insights and attitudes toward clients, counseling service objectives, counseling service settings, technical implementation of counseling services, and evaluation of counseling services. The focus of counseling services has remained the same from time to time, but only the context of the focus of counseling services continues to experience development.